Assessing the Effectiveness of the UNSC’s Role in Global Governance - Indah Dian Nurani S; Ali Maksum (Universitas Medan Area, 2026)
The United Nations Security Council (UNSC) occupies a central position in global governance as the primary institution responsible for maintaining international peace and security. Despite its extensive legal authority, the effectiveness of the UNSC has been persistently questioned, particularly in addressing protracted humanitarian conflicts. This study examines the effectiveness of the UNSC in global governance by focusing on the Palestine-Israel conflict as a critical case that reflects broader structural and political constraints within the Council. Employing a qualitative library research method, this study analyzes official United Nations documents, including UNSC resolutions, voting records, and meeting reports, alongside peer-reviewed academic literature and policy reports from international organizations and non-governmental organizations. The analysis is guided by realism and neoliberal institutionalism as complementary theoretical frameworks to explain the interaction between power politics and institutional mechanisms within the UNSC. The findings indicate that the effectiveness of the UNSC is significantly hindered by the veto power of the permanent members, particularly when national interests override humanitarian considerations. Nevertheless, the UNSC continues to function as an important normative forum that facilitates dialogues and sustains international legal and moral frameworks for conflict resolution. This study argues that without meaningful institutional reform and greater inclusivity, the UNSC’s role in global governance will remain normatively influential but operationally limited.